Assessing Market and Financial Feasibility of Shoe Cleaning Services: A Case Study of Shoes Cleaner Cikarang - Satria, I Gede Yohanes E; Pramita, Yunia; Utari, Vita Tri; Malik, Abdul; Pitaloka, Okka Chandra; Muktar, Ramdani (Review: Journal of Multidisciplinary in Social Sciences, 2025)
This business feasibility study aims to analyze the potential of a shoe cleaning business, Shoes Cleaner Cikarang, with a focus on marketing and financial aspects. In the context of modern lifestyles, clean shoes are an important part of appearance, especially among young people and professionals. The high level of public busyness creates a need for practical and efficient services in shoe care. Shoes Cleaner, located in Cikarang and established in 2023, offers shoe cleaning services with two types of treatments: fast clean and deep clean. Through marketing analysis, this study identified a target market consisting of young people, professionals, owners of popular shoe brands, and urban communities. The marketing strategy implemented includes the use of social media for promotions and discount offers. This study uses a qualitative method with a descriptive approach. This method focuses on interpretive and non-numerical analysis of social phenomena occurring at Shoes Cleaner Cikarang. Data collection was carried out through interviews and documentation to produce an accurate and objective picture of the business condition and its market potential. From a financial aspect, analysis using the net present value (NPV), payback period (PP), and internal rate of return (IRR) methods indicates that this business is feasible. The calculation results show an NPV of Rp. 24,326,294.16, a payback period of 9 months, and an IRR of 131.32%, indicating significant profit potential.